Purchasing Decisions on Blibli e-Commerce: Can Influencer Marketing, Brand Image, and Trust Make an Impact? - Cornellya, Vonny; Khoiri, M (Universitas Batanghari, 2024)
This research aims to test and analyze the influence of influencer marketing, brand image, and trust on purchasing decisions on Blibli e-commerce in Batam City. This type of research is quantitative research. The variables in this research are influencer marketing, brand image, trust, and purchasing decisions. The population in this research is the people of Batam City. The data in this study was collected using a questionnaire prepared using a Likert scale measurement scale. The total number of research samples was 204 samples. The data analysis technique uses multiple linear regression with the help of the SPSS program. The findings of this research show that influencer marketing, brand image, and trust positively and significantly influence purchasing decisions on Blibli e-commerce.